PO89 | Apixaban for secondary prevention of venous thromboembolism in hemodialysis patients: pharmacokinetic profile and safety outcomes (Bleeding, Thrombosis and Vascular Biology)
Background and Aims: The use of direct oral anticoagulants (DOACs) in patients with end-stage renal disease (ESRD) on dialysis remains controversial due to a different pharmacokinetics. To date, dialysis patients have been excluded from all randomized clinical trials and data on these setting are scanty. Among DOACs, apixaban has shown the most favorable profile in this population. We report the case of a female dialysis patient with a history of unprovoked pulmonary embolism and deep vein thrombosis, previously treated with vitamin K antagonists (VKAs), than shifted to apixaban low-dose (2.5 mg twice daily) due to hemorrhagic complications while on VKAs; we focus on apixaban plasma levels and safety outcomes during follow-up.